EKSISTENSI BUDAYA LOCAL DALAM PENDIDIKAN KARAKTER DI ERA MODERNISASI - Sadiana, I Made; Rahmawati, Ni Nyoman (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2024)
ABSTRACT The purpose of this writing is to examine the existence of local culture in character education during the era of modernization. Character education is a matter of utmost urgency and importance for the younger generation in the midst of increasingly sophisticated technological advancements. This progress not only brings positive influences but also negative ones, such as the erosion of the nation's moral values due to the influence of foreign cultures that may not align with the nation's noble values. To fortify the younger generation against various negative impacts of technological progress, local culture, as one of the systems of values growing and evolving within a society based on religious teachings, morality, and intergenerational experiences, is crucial as a moral foundation in shaping the character of the nation's children. This aims to cultivate a young generation with noble behavior, integrity, religious values, and empathy towards various issues in their surrounding environment. Keywords: Existence, Local Culture, Character Education, Modernization